The planning of tourism on rural areas: The stakeholders' perceptions of the Boticas municipality (Northeastern Portugal) - Remoaldo, Paula (2017)
Most of the strategies developed to “save” rural te rritories in Europe have not been successful. One of their main problems has been the adoption of the top-down paradigm when approaching the development of those territories. P ortugal is a good example of the difficulty of adopting a bottom-up paradigm. The main objectiv e of this paper is to present the perceptions of the local (including the residents) and regional stakeholders acting at Boticas regarding the set of resources available and the de velopment of the tourism industry. Boticas is a Northern Portuguese rural low density municipa lity. In capturing those perceptions, the research contributes to the establishment of a more integrated and innovative development strategy and thus a more able strategy for profitin g from the potential associated with the growing of the tourism industry experienced recentl y by Portugal. The adoption of a mixed- method for evaluating these resources and capturing the perceptions of the tourist potential by the different stakeholders is suggested. Empiric al data was collected through a survey of 373 of its residents and 25 interviews conducted wi th local and regional actors, further supported by an inventory of the cultural resources and their capacity for visits. We conclude here that residents tend to have a very positive pe rception of tourism development, and indeed, their perceptions largely met those of othe r stakeholders.